CURC 2023 - Colorado State University. JUR Press, publisher (Colorado State University. Libraries, 2023)
Abstracts from the CURC 2023 Showcase.
Celebrate Undergraduate Research and Creativity at Colorado State University: showcase 2023
Showcase 2023
CURC is generously supported by the Office for Undergraduate Research and Artistry, The Institute for Learning and Teaching and CSU's School of Music Theater and Dance.
Keywords: Colorado State University -- Undergraduates -- Research; Undergraduates -- Research -- Colorado -- Fort Collins